History of the kyrgyz family and forms of marriage (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article describes the history of the Kyrgyz family and the form of marriage. Most of the research is devoted to the Soviet and before Soviet times. The relevance of the study is due to the fact that in order to introduce the concept of the values of Kyrgyz customs and traditions in marriage to modern society. The family structure of Kyrgyz society, the process of entering into a marriage in society requires deep theoretical and practical research. It is a modern requirement to study the forms of marriage and family of the Kyrgyz people and their history, the direction of growth and development, their place in our lives.
Keywords: marriage; ethnos; matriarchy; patriarchy; exogamy; endogamy; family